In appreciation of an ingenious scientist and a great friend: Győző Garab - Govindjee, G (Photosynthetica, 2023)
To express my appreciation of Győző Garab, I describe below our association over the years, followed by a brief description of his fundamental research in the area of biophysics of photosynthesis.
Keywords: Hartmut Lichtenthaler; Wolfgang Junge; Hartmut Michel; Jan Anderson; Rajni Govindjee; Reto Strasser; Paul Mathis